Elizabeth Wentworth, Countess of Strafford, and her Role in the Vice-Regal Household in Ireland. (4th May 2021) - Pogson, Fiona
Abstract : One of the early Stuart vicereines of Ireland, Elizabeth Wentworth, countess of Strafford, contributed significantly to the expression of vice-regal honour during her husband's deputyship. This article draws attention firstly to her work in establishing and maintaining the household of the lord deputy, or viceroy, including her responsibilities in caring for stepchildren and her fulfilment of charitable duties. Secondly, it discusses the ways in which she was presented to others on public occasions. It argues that these interactions were guided in part by Lord Deputy Wentworth's understanding of older conventions governing the conduct of the governor's wife, but also influenced by the more recent significance attached to the role of the queen-consort, underlined by the appearance of a portrait of Henrietta Maria in Dublin Castle and its role in Wentworth's inauguration ceremony.